Platelet monoamine oxidase activity in diabetics. - Maria Azevedo; Francisca Fernandes; Pedro Lisboa; Carlos Manso (Acta Médica Portuguesa, 1980)
Platelet monoamine oxidase (MAO) activity was determined, using benzylamine as substract. Results are expressed as nM benzaldehyde/mg protein hour, at 37”. A total of 79 diabetics (40 M and 39 F) ranging in age from 3 to 70 years was studied. A normal control group included 39 persons (17 M and 22 F) ranging in age from 16 to 60 years. Piatelet MAO activity shows a slight variation in relation to age (not significant). But, in each age group, diabetics have an increased activity in comparison with normals. MAO activity of the plasma shows no significant difference in relation to age or sex, but the values for diabetics are approximately twice the normal. The activity of MAO in platelets shows a significant increase in activity in diabetics of either sex, in comparison to normal individuals. Besides, women show a significantly increased activity. No relationship was found between platelet MAO activity of young vs old diabetics, juvenile onset: insulin vs non insulin treated, duration of the disease, or presence vs absence of retinopathy.